Intention to Visit Uttarakhand among Potential Young Indian Travelers: Travel Motivations, Perceived Risks and Constraints ((PJHAS) PUSA Journal of Hospitality and Applied Sciences, 2024)
Background: Uttarakhand, often called the "Land of Gods," is renowned for its breathtaking landscapes, spiritual  heritage, and adventure opportunities. Despite its potential, young Indian travellers aged 18–25 face diverse motivations  and deterrents that shape their travel decisions. Understanding these factors is vital for enhancing Uttarakhand’s appeal  among this demographic. Objectives: The primary objective of this study is to investigate the travel intentions of young  Indian travelers by examining the factors that motivate them to visit Uttarakhand, alongside the perceived risks and  constraints that deter them. Methodology: A survey-based descriptive research design was adopted, collecting data  from 100 respondents at a hospitality institute in Delhi through structured questionnaires using Google Forms via  one-on-one interactions. Statistical tools, including frequency distribution and Chi-Square analysis, were employed  to examine relationships between variables. Results: The findings indicate that natural beauty (38%) and adventure  experiences (25%) are the top motivators for travel, while religious motivations are less influential. The relationship  between variables: such as gender, travel motivations (χ² = 3.84, p = 0.43), seasonal preferences (χ² = 12.51, p = 0.70),  and perceived risks (χ² = 12.15, p = 0.016). There is no significant relationship between gender and primary travel  motivations (p > 0.05), nor between travel motivations and preferred seasons (p > 0.05). However, natural disasters  emerged as a significant perceived risk (p < 0.05), deterring travel and increasing the preference for sustainable tourism.  Time and budget constraints significantly shape transportation preferences, favoring buses and personal vehicles. Short  stays (
Keywords: Uttarakhand; young travellers; travel motivation; perceived travel risks; travel constraints; tourism; responsible tourism